ADAM‐C score: New risk score for predicting diagnostic yield of transesophageal echocardiography after cerebral ischemia. Issue 8 (14th May 2018) - Charbonnel, Clément; Jego, Christophe; Jourda, François; Vinsonneau, Ulric; Garçon, Philippe; Turlotte, Guillaume; Rivière, Jean François; Maurin, Marion; Lubret, Rémy; Meimoun, Patrick; Akret, Chrystelle; Cournot, Maxime; et al.
Abstract : Background and aim: The clinical utility of transesophageal echocardiography (TEE) after brain ischemia (BI) remains a matter of debate. We aimed to evaluate the clinical impact of TEE and to build a score that could help physicians to identify which patients should better benefit from TEE. Methods: This prospective, multicenter, observational study included patients over 18 years old, hospitalized for BI. TEE findings were judged discriminant if the results showed important information leading to major changes in the management of patients. Most patients with patent foramen ovale were excluded. Variables independently associated with a discriminant TEE were used to build the prediction model. Results: Of the entire population (1479 patients), 255 patients (17%) were classified in the discriminant TEE group. Five parameters were selected as predictors of a discriminant TEE. Accordingly, the ADAM‐C score could be calculated as follows: Score = 4 (if age ≥60) + 2 (if diabetes) + 2 (if aortic stenosis from any degrees) + 1 (if multi‐territory stroke) + 2 (if history of coronary artery disease). At a threshold lower than 3, the sensitivity, specificity, positive predictive value, and negative predictive value (NPV) of detecting discriminant TEE were 88% (95% CI 85–90), 44% (95% CI 41–47), 21% (95% CI 19–27), and 95% (95% CI 94–97), respectively. Conclusion: A simple score based on clinical and transthoracic echocardiographic parameters can help physicians to identify patients who might not benefit from TEE. Indeed, a score lower than 3 has an interesting NPV of 95% (95% CI 94–97).